Precipitation Impacts on Agricultural Production in Afghanistan - Safi, Abdul Ghias; Safi, Lutfullah (Journal of Natural Sciences – Kabul University, 2024)
Agricultural production is vital for the survival and sustainability of every nation and its population, and any disruption to this sector poses significant challenges to human life. In recent decades, Afghanistan has experienced a general decline in agricultural production, primarily due to climate change and rapid population growth. Each year, a substantial portion of the country’s rainfall flows beyond its borders without being utilized effectively. Moreover, local communities often suffer extensive damage from floods caused by unmanaged rainfall. If the relationship between precipitation and agricultural production in Afghanistan is not thoroughly studied, the country will fail to maximize the benefits of its limited rainfall resources. This study evaluates the effects of rainfall on Afghanistan's agricultural production by analyzing long-term data on precipitation and crop yields. The findings provide insights into the challenges faced by the agricultural sector and offer recommendations aimed at enhancing national interests through more effective water management and agricultural practices.